The Effect of Coconut Shell Liquid Smoke Concentration and Drying Duration on the Chemical Characteristics and Organoleptic Properties of Analog Jerky - Azzahra, Raidza; Ratna Yulistiani (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
This study aims to determine the optimal treatment combination of coconut shell liquid smoke concentration and drying duration for the chemical and organoleptic characteristics of oyster mushroom and red bean analog jerky. This study employs a completely randomized design (CRD) with a two-factor factorial structure and three replications. Factor I: concentration of coconut shell liquid smoke (0%, 0.5%, and 1%) and Factor II: drying duration (5 hours, 6 hours, and 7 hours). The chemical data were examined using ANOVA and the Duncan's Multiple Range Test (DMRT) to see if there were significant differences at a 5% level, while the taste and smell data were checked with the Friedman test at the same 5% level. The best results were found with a coconut shell liquid smoke concentration of 0.5% and a drying time of 6 hours, showing 12.48% moisture, 1.04% ash, 20.62% protein, and 10.96% fat, along with preference scores of 2.5 for color (dislike), 3.04 for aroma (like), 3.2 for taste (like), and 3.16 for texture (like). Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well-BeingSDG 12: Responsible Consumption and Production